Pigmented basal cell carcinoma diagnosed in a dental setup: Report of a case with review of the literature - Snehashish Ghosh; Safal Dhungel; Indu Bharkavi; Bhawana Subedi Sapkota; Prabesh Banstola (Clinical Case Reports)
Abstract Pigmented basal cell carcinoma is a rare variant of basal cell carcinoma, with only a limited number of reported cases. Because of its similar clinical presentation, it is often over‐diagnosed as malignant melanoma. Along with case presentation, the clinical, microscopic features, and differential diagnosis are discussed in this case report.